Updating the genomic taxonomy and epidemiology of Campylobacter hyointestinalis - Wilkinson DA; O'Donnell AJ; Akhter RN; Fayaz A; Mack HJ; Rogers LE; Biggs PJ; French NP; Midwinter AC (Springer Nature Limited, 2018)
Campylobacter hyointestinalis is a member of an emerging group of zoonotic Campylobacter spp. that are increasingly identified in both gastric and non-gastric disease in humans. Here, we discovered C. hyointestinalis in three separate classes of New Zealand ruminant livestock; cattle, sheep and deer. To investigate the relevance of these findings we performed a systematic literature review on global C. hyointestinalis epidemiology and used comparative genomics to better understand and classify members of the species. We found that C. hyointestinalis subspecies hyointestinalis has an open pangenome, with accessory gene contents involved in many essential processes such as metabolism, virulence and defence. We observed that horizontal gene transfer is likely to have played an overwhelming role in species diversification, favouring a public-goods-like mechanism of gene ‘acquisition and resampling’ over a tree-of-life-like vertical inheritance model of evolution. As a result, simplistic gene-based inferences of taxonomy by similarity are likely to be misleading. Such genomic plasticity will also mean that local evolutionary histories likely influence key species characteristics, such as host-association and virulence. This may help explain geographical differences in reported C. hyointestinalis epidemiology and limits what characteristics may be generalised, requiring further genomic studies of C. hyointestinalis in areas where it causes disease.
Keywords: Bacterial evolution; Bacterial genomics; Pathogens